2018
DOI: 10.1002/cphc.201800733
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Quantum Atoms Approach and Electrostatic Solvation Energy: Assessing Atomic and Group Solvation Contributions

Abstract: The interacting quantum atoms (IQA) method decomposes the total energy of a molecular system in terms of one‐ and two‐center (atomic) contributions within the context of the quantum theory of atoms in molecules. Here we incorporate electrostatic continuum solvent effects into the IQA energy decomposition. To this end, the interaction between the solute electrostatic potential and the solvent screening charges as defined within the COSMO solvation model is now included in a new version of the PROMOLDEN code, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For this endeavour, one would have to consider how either the solvent or peptidic surroundings modify the one‐ and two‐particle density matrices of the examined excited states. Some progress in this direction has been made, as in the case of solvent effects in a continuum approximation for GSs [86] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this endeavour, one would have to consider how either the solvent or peptidic surroundings modify the one‐ and two‐particle density matrices of the examined excited states. Some progress in this direction has been made, as in the case of solvent effects in a continuum approximation for GSs [86] …”
Section: Resultsmentioning
confidence: 99%
“…Some progress in this direction has been made, as in the case of solvente ffects in ac ontinuum approximation for GSs. [86]…”
Section: Perspectivesmentioning
confidence: 99%
“… 21 Furthermore, it has been shown that the IQA net atomic energies can easily absorb the electrostatic continuum-solvent effects, allowing thus the partition of solvation energies into effective atomic and group contributions. 22 …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the Interacting Quantum Atoms methodology 21,22 (IQA) was employed, which has so far been successfully utilized for analysis of diverse systems, properties and processes. 23–41 It enables quantification of classical and non-classical interaction terms among selected fragments (the fragments being BN & PCH + , BN & H + , PC & H + , or BN & H + & PC), but also energetical properties of the fragments themselves when their geometry and the environment modify upon reaction advancement. The paper is organized as follows: Section 2 contains details of the computational procedure; the results and their discussion are presented in Section 3; the conclusions are summarized in Section 4.…”
Section: Introductionmentioning
confidence: 99%